Campos eletromagnéticos e tecido ósseo: determinação de parâmetros para tratamento de fraturas - Natália Valente Moreira (2020)
Bone fractures are a public health problem with high socioeconomic impact. The use of physical stimulation therapies is growing as a way to facilitate bone callus formation in fractures. The purpose of this study was to determine the role and effectiveness of using electromagnetic fields in the treatment of bone fractures. The study was divided into three steps: a systematic review in humans, a systematic review in animal studies, and a computational simulation. The search for studies for the review steps was conducted in MEDLINE, LILACS, and Physiotherapy Evidence Database (PEDro) databases, including studies published between the years 1970 to 2020. The first stage included randomized clinical trials in humans diagnosed with acute or chronic long bone diaphysial fractures, and the second stage included studies in mammals with osteotomy-induced fractures and/or bone lesions that presented a control group. Methodological quality was assessed using the PEDro scale in human studies. In the third step a simulation was performed to analyze the magnetic field distribution over the bone tissue, through the Finite Element Method Magnetics software an axisymmetric model with approximate dimensions of a human leg was elaborated. The systematic review in humans resulted in eleven studies with moderate to high methodological quality and the review in animals resulted in eighteen studies. In human studies, clinically positive results were found for acute and chronic fractures, and with statistical relevance only for chronic fractures, where bone healing was investigated as the primary outcome. Most animal studies have shown positive results with statistical relevance for the outcome of bone callus formation. In computational simulation the magnetic field distribution can be considered almost uniform as a function of the position of bone tissue in the analyzed model. It can be concluded that low frequency pulsed electromagnetic field devices are effective in healing chronic fractures in humans and in decreasing pain, improving range of motion, and functionality in individuals with acute fractures. Computational simulation has proven to be an important tool to aid and optimize research on low frequency electromagnetic field distribution in bone tissue.